Kosztolányi Dezső Kína-képe - Kalmár, Éva (Studia Litteraria, 2018)
Hungarian poet and writer Dezső Kosztolányi edited and translated the first anthology of Chinese classical poetry in the 20th century, entitled Chinese and Japanese Poems, which was published at the end of 1931. But his interest in Chinese culture can be traced back to much earlier, to the first decade of the 20th century. This article takes into consideration all of Kosztolányi’s prose writings, articles and translations related to China, Chinese poetry and also the sources of his knowledge about China, published in Hungarian and in english, German and French, such as the books of H. A. Giles, arthur Waley, richard Wilhelms, Paul Claudel and others. The paper also analyzes the role of anthologies of Chinese poetry in foreign languages that Kosztolányi consulted for his translations into Hungarian. in his writings, he depicted a somewhat idealistic picture of Chinese culture, and in spite of some occasional errors, he was successful in describing some important characteristics of Chinese life of the past, and his writings and translations have had a great influence in Hungary.